Pozostałości pieców w osiemnastowiecznym królewskim pałacu podróżnym w Kutnie - Lechowicz, Zbigniew (Acta Universitatis Lodziensis. Folia Archaeologica, 2010)
Royal Travelling Palace was built after 1750 when a parcel, within which the ruler had to build dwelling buildings for his convenience was hired. The complex consisted of a palace with two side wings, two free-standing outbuildings, garden-park arrangement and two economic buildings. In 2004 archaeological excavations within the object were conducted, which aimed at completing the knowledge on the palace and completing the data about its building phases were conducted. In the course of the works 7902 fragments of movables were obtained, such as clay vessels, tiles, glass and metal objects, animal bones and others. Among an interesting collection of tiles, including 1047 fragments, only 8 fragments of vessel-like specimens were distinguished. Plate tiles were divided into groups considering mainly their ornamentation. The main part of the collection is composed by specimens with cartouche ornament. Their faces arc most often covered with white glaze. Layers, in which such fragments were found arc connected with the oldest building phase of the Saxon palace dated to 1750. Filling and moulding specimens were distinguished. On the grounds of finds of tiles of such type within trench X a reconstruction of the stove was made, which may have been placed in one of the rooms of the western palace wing. Less numerous group was created by fragments of tiles in similar stylistics, covered with green glaze. These finds are dated to the 2nd half of the 18th century. Also fragments of tiles, plates of which were decorated with wealthy vegetal motifs characteristic of the 17th century ornamentation were distinguished. Specimens were covered with green and olive glazes. The last group included the 19th century specimens of plain, unornamented plates covered with green glaze. Remains of heating equipment were stated in side wings of the palace and in the central break. This discovery will probably help the works on reconstruction of stoves functioning in the palace.